2021
DOI: 10.3390/jcm10030434
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Periprosthetic Joint Infection in Primary Total Hip Arthroplasty Using Pre-Operative Chlorhexidine Bathing

Abstract: Periprosthetic joint infection (PJI) after total hip arthroplasty (THA) is a devastating complication. The aim of this study was to investigate whether preoperative bathing using chlorhexidine gluconate (CHG) before THA can effectively reduce the postoperative PJI rate. A total of 933 primary THA patients, with the majority being female (54.4%) were included in the study. Primary THA patients who performed preoperative chlorhexidine bathing were assigned to the CHG group (190 subjects), and those who did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The present study showed that patients in the study group had significantly shorter stay in hospital, less treatment cost, less score of symptom check after interventions, better hip joint function, higher nursing satisfaction, and lower incidence of side effects than those in the control group, and the difference was statistically significant (p < 0.05). Consistent with the previous reports (both local and international) these results indicate that the clinical nursing pathway has a considerable advantage in the clinical nursing practice for patients with artificial hip arthroplasty [23][24][25]. However, in practical setting, it is also important to note that treatment and care should be strictly carried out according to the scheduled timetable.…”
Section: Indicatorssupporting
confidence: 88%
“…The present study showed that patients in the study group had significantly shorter stay in hospital, less treatment cost, less score of symptom check after interventions, better hip joint function, higher nursing satisfaction, and lower incidence of side effects than those in the control group, and the difference was statistically significant (p < 0.05). Consistent with the previous reports (both local and international) these results indicate that the clinical nursing pathway has a considerable advantage in the clinical nursing practice for patients with artificial hip arthroplasty [23][24][25]. However, in practical setting, it is also important to note that treatment and care should be strictly carried out according to the scheduled timetable.…”
Section: Indicatorssupporting
confidence: 88%